Dampak Ideologi Liberalisme terhadap Pola Pikir Umat Islam - Rina Setyaningsih; Rohmawati Rohmawati; Vitaloka Vitaloka; Ainun Ni'mah; Ramdan Hadi; Siti Rahmadan Ningsih; Mei Andri Yani (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Liberalism and Islamare two ways in different directions. Although both are often juxtaposed in every discussion of scholars, it is very difficult to put together. Islamis a religion that is assumed to the word of God through"the"book"of"the"Quran"and the hadith"of"the"Apostle, where each of its adherents has boundaries in carrying out life to survive in the world and the hereafter, while liberalism comes as an ideology that emphasizes the rights and freedom of every individual in all aspects of life including religion. This journal aims to present knowledge about"the"impact"of the ideology of liberalism"on"the"thought"of"the"Islamic Ummah. This study involved related literature analysis of academic sources, including theoretical works and thoughts of scholars andIslamicthinkers."The"conclusion"that"can"be"drawn"from"this"study"isthat"the"understanding"of"liberalism is still widely adopted by the Islamic Ummah even though the ideology of liberalism is very"contrary"to"the"teachings"of"Islam", this"is"due"to"the"weak religious education in every individual of the Islamic Ummah itself which then considers that Islamic rules curb human freedom.